The Effect of Capital Expenditure, Local Own Revenue, Audit Opinions, and Audit Findings on Corruption - Febrina Amelia Valentina; Tri Joko Prasetyo; Sari Indah Oktanti Sembiring (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Corruption in the public sector remains a major obstacle to regional development, threatening the effectiveness of financial management and public services. Gaps in financial supervision and management that are not transparent are the cause of fraud in the use of the budget. The agency theory states that corruption is caused by a conflict of interest between the community as the principal and the government as an agent, with the external auditor as a supervisor to prevent irregularities. The focus of this research is to find out the relationship between corruption in local governments and capital expenditure, local own revenue, audit opinions, and audit findings. This study uses quantitative methods and uses secondary data. The sample consistSed of 250 local governments (districts/cities/provinces) in Indonesia during 2020-2022. The analyst method uses SPSS 27 with multiple linear regression method. The test results showed that capital expenditure had no effect on corruption, local own revenue and audit findings had a positive effect on corruption, and audit opinions had nothing to do with corruption in local governments.